IDENTITY OF STAPHYLOCOCCUS EPIDERMIDIS - Jones, Dorothy (J Bacteriol, 1963)
Jones, Dorothy (American Meat Institute Foundation, Chicago, Ill.), R. H. Deibel, and C. F. Niven, Jr. Identity of Staphylococcus epidermidis. J. Bacteriol. 85:62–67. 1963.—The species Staphylococcus epidermidis is defined more precisely, and compared with other staphylococci. The physiological characteristics considered to be of primary import are: (i) ability to grow anaerobically in a defined complex medium with glucose or pyruvate as the energy source; (ii) inability to produce coagulase; (iii) ability to ferment serine as an energy source; (iv) the requirement for biotin and uracil (under anaerobic conditions) in a semisynthetic medium; and (v) inability to reduce nitrate beyond nitrite.